ROBOTIC FLEXIBLE URETEROSCOPY VERSUS CONVENTIONAL FLEXIBLE URETEROSCOPY FOR THE MANAGEMENT OF RENAL CALCULI: EFFICACY, SAFETY, AND COST EFFICIENCY A SYSTEMATIC REVIEW - Anita Arum Wijayatri; John M.Sangkai (International Medical Journal Corp. Ltd, 2026)
Introduction: Robotic flexible ureteroscopy (R-fURS) has been developed to overcome ergonomic and technical limitations of conventional flexible ureteroscopy (C-fURS) for renal calculi. This systematic review compares the efficacy, safety, and cost efficiency of R-fURS versus C-fURS. Methods: A systematic search of PubMed, Scopus, Cochrane Library, Web of Science, and ClinicalTrials.gov (up to April 2026) was conducted following PRISMA 2020 guidelines. Risk of bias was assessed using RoB 2 (RCT) and ROBINS-I (observational studies). Certainty of evidence was evaluated using GRADE. Meta-analysis was not performed due to clinical and methodological heterogeneity. Results: Four studies comprising 518 patients were included: one head-to-head RCT (Geavlete 2016, N=132) and three single-arm R-fURS studies (Salah 2024, Kim 2025, Klein 2021). R-fURS stone-free rates ranged 73–92.4%, comparable to C-fURS (89.4% in direct comparison). Major complications (Clavien-Dindo ≥III) were 0–1%. Operative time ranged 51–116 minutes; length of stay was 9.3 hours–1.5 days. No study reported explicit cost data. Consistent advantages of R-fURS included improved surgeon ergonomics and reduced radiation exposure. Overall GRADE certainty: Very Low to Low. Discussion: R-fURS achieves comparable stone-free rates and safety to C-fURS, with superior ergonomics and radiation protection as its most robust benefits. However, evidence is limited by heterogeneity in stone-free rate definitions, lack of direct comparative data, and absence of cost-effectiveness analyses. Conclusion: R-fURS is a feasible alternative to C-fURS with acceptable efficacy and safety. Large-scale multicentre RCTs with standardised outcomes and formal cost analyses are required before strong clinical recommendations can be made.